An investigation on visual and audiovisual stimulus based emotion recognition using EEG - Murugappan, M.; Mohd Rizon, Mohammed Juhari; Nagarajan, Ramachandran, Prof. Dr.; Sazali, Yaacob, Prof. (Inderscience Enterprises Ltd., 2010)
Link to publisher's homepage at http://www.inderscience.com/